2018
DOI: 10.18203/2394-6040.ijcmph20181219
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of refractive errors among school children in the rural field practice area of a tertiary care hospital, Bengaluru

Abstract: Background: An estimated 19 million children are visually impaired, and 12 million are visually impaired due to refractive errors. Children fall in preventable age group for correction of refractive errors. Schools are best forum for implanting health education for children and for early detection of ocular morbidity. This study was undertaken to assess the prevalence of refractive errors among school children in rural field practice area of Rajarajeswari Medical College and Hospital, Bengaluru.Methods: A cros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
11
4

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 4 publications
4
11
4
Order By: Relevance
“…4 Another study in India reported myopia followed by astigmatism and lastly hyperopia (58.5%, 24.4%, and 17.1% respectively). 11 On the other hand, our finding agrees with Hashemi H (2017) finding in systematic review and meta-analysis that astigmatism was the most common refractive error in children. 12 This variation can be explained by using different methods in the evaluation of RE type.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…4 Another study in India reported myopia followed by astigmatism and lastly hyperopia (58.5%, 24.4%, and 17.1% respectively). 11 On the other hand, our finding agrees with Hashemi H (2017) finding in systematic review and meta-analysis that astigmatism was the most common refractive error in children. 12 This variation can be explained by using different methods in the evaluation of RE type.…”
Section: Discussionsupporting
confidence: 92%
“…4 Also, lower figure was reported by Vidusha KS (2018) in India, as the prevalence rate was 10.5% in a study included 1140 school children aged 7-16. 11 This difference in finding may be due to different study design, sample size and/or age of students included in the study. The present study revealed that only 35.7% of RE students wore glasses before our screening which was significantly higher in private school children 74.3% of RE students.…”
Section: Discussionmentioning
confidence: 97%
“…This is much higher than studies conducted in rural Bangalore (10.5%), Goa (18.0%), Mangalore (14.2%) and Shimla (31.6%). 3,[7][8][9] In another study on ocular morbidity and its associates among Madrasah students of Kolkata, the overall prevalence of ocular morbidity was 12.67% with refractive error being the commonest (9.40%). 10 These differences may be attributed to the difference in sample size, wider age groups covered and setting of these studies as compared with our study.…”
Section: Discussionmentioning
confidence: 99%
“…In a study by Khandekar et al, boys had the higher uncorrected refractive error, although gender was not significantly associated with uncorrected refractive error in urban and rural children. [11] In contrast, studies by Vidusha KSS et al [15] Prema N et al…”
Section: Discussionmentioning
confidence: 95%
“…Similarly, many studies reported an increase in the prevalence of refractive error with increasing age. [13,14,15] In contrast, Khandekar et al…”
Section: Discussionmentioning
confidence: 99%